2020
DOI: 10.1212/wnl.0000000000009989
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucocerebrosidase activity in GBA -linked Parkinson disease

Abstract: Objective:To test the relationship between clinically relevant types of GBA mutations (none, risk variants, mild mutations, severe mutations) and β-glucocerebrosidase activity in patients with Parkinson's disease (PD) in cross-sectional and longitudinal case-control studies.Methods:481 participants from the Harvard Biomarkers Study (HBS) and the NIH Parkinson Disease Biomarkers Program (PDBP) were analyzed, including 47 PD patients carrying GBA variants (GBA-PD), 247 without a GBA variant (idiopathic PD), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Enzymatic activity of GCase seems to be a promising biomarker in GBA -PD, showing a genotype–phenotype association. Lower GCase enzymatic activity measured in dried blood spots has been reported in GBA -PD patients compared with noncarriers ( 64 ), and after genotypic stratification for GBA variants, increasing severity was associated with decreasing residual GCase activity ( 22 , 62 , 65 ) and longitudinally with a steeper decline of enzymatic activity ( 65 ). When measured in CSF, GCase activity was again significantly reduced in GBA -PD ( 66 ).…”
Section: Genotype–phenotype Correlation With Nonclinical Biomarkers In Gba -Parkinson Diseasementioning
confidence: 86%
“…Enzymatic activity of GCase seems to be a promising biomarker in GBA -PD, showing a genotype–phenotype association. Lower GCase enzymatic activity measured in dried blood spots has been reported in GBA -PD patients compared with noncarriers ( 64 ), and after genotypic stratification for GBA variants, increasing severity was associated with decreasing residual GCase activity ( 22 , 62 , 65 ) and longitudinally with a steeper decline of enzymatic activity ( 65 ). When measured in CSF, GCase activity was again significantly reduced in GBA -PD ( 66 ).…”
Section: Genotype–phenotype Correlation With Nonclinical Biomarkers In Gba -Parkinson Diseasementioning
confidence: 86%
“…GBA encodes the β-glucocerebrosidase enzyme that hydrolyzes the substrate glucosylceramide. In PD patients, increasing severity of the type of GBA mutation is quantitatively associated with decreasing β-glucocerebrosidase activity 4 , increased risk of developing PD 5 , and more rapid cognitive decline 2 , 6 . We and others 6 previously reported that neuropathic Gaucher’s disease (GD) mutations are linked to rapid cognitive decline in PD patients 2 , 6 – 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous variants in the GBA gene have been associated with lower GCase activity using a variety of assays in different tissues including blood, CSF, postmortem brain, and induced pluripotent stem cell–derived neurons 25‐29 . Importantly, residual GCase activity in blood was recently reported to be inversely associated with mutation severity, with severe GBA mutations showing the lowest GCase enzyme activity 30 . These findings from the Havard Biomarkers Study and the NINDS Parkinson's Disease Biomarker Program along with the results from TUEPAC‐MIGAP and PPMI robustly confirm that the type of GBA mutation influences GCase enzyme activity in PD.…”
Section: Discussionmentioning
confidence: 99%